2008
DOI: 10.1124/jpet.108.139295
|View full text |Cite
|
Sign up to set email alerts
|

N-((1S)-1-{[4-((2S)-2-{[(2,4-Dichlorophenyl)sulfonyl]amino}-3-hydroxypropanoyl)-1-piperazinyl]carbonyl}-3-methylbutyl)-1-benzothiophene-2-carboxamide (GSK1016790A), a Novel and Potent Transient Receptor Potential Vanilloid 4 Channel Agonist Induces Urinary Bladder Contraction and Hyperactivity: Part I

Abstract: The transient receptor potential (TRP) vanilloid 4 (TRPV4) member of the TRP superfamily has recently been implicated in numerous physiological processes. In this study, we describe a small molecule TRPV4 channel activator, (N-, which we have used as a valuable tool in investigating the role of TRPV4 in the urinary bladder. GSK1016790A elicited Ca 2ϩ influx in mouse and human TRPV4-expressing human embryonic kidney (HEK) cells (EC 50 values of 18 and 2.1 nM, respectively), and it evoked a dose-dependent activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
306
4
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 360 publications
(340 citation statements)
references
References 40 publications
(66 reference statements)
20
306
4
2
Order By: Relevance
“…At this point, we cannot exclude that inhibition of TRPV4 in other cell types contributes to the observed effects of HC-067047 on bladder function. In the bladder, TRPV4 is also expressed in the detrusor muscle layer, albeit at an ∼20-fold lower expression level than in urothelium (13), and in endothelial cells surrounding blood vessels. Moreover, TRPV4 expression has been documented in dorsal root ganglion neurons innervating the viscera and has been implicated in tonicity-induced neurogenic inflammation and release of substance P and calcitonin gene-related peptide (CGRP) from bladder tissue (29,30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At this point, we cannot exclude that inhibition of TRPV4 in other cell types contributes to the observed effects of HC-067047 on bladder function. In the bladder, TRPV4 is also expressed in the detrusor muscle layer, albeit at an ∼20-fold lower expression level than in urothelium (13), and in endothelial cells surrounding blood vessels. Moreover, TRPV4 expression has been documented in dorsal root ganglion neurons innervating the viscera and has been implicated in tonicity-induced neurogenic inflammation and release of substance P and calcitonin gene-related peptide (CGRP) from bladder tissue (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has identified TRPV4 as an important regulator of normal bladder function (12)(13)(14)(15)(16)25), but its involvement in the development of cystitis and the associated changes in bladder function was unknown. In this article, we show that the development of reduced functional bladder capacity and pollakisuria after cyclophosphamide treatment is strongly impaired in Trpv4 −/− mice, despite clear signs of severe hemorrhagic cystitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using fluorescence ratiometric imaging of the Ca 2ϩ -sensitive probe, fura-2, [Ca 2ϩ ] i was monitored and presented as the ratio F 340 /F 380 (or [Ca 2ϩ ] i in summary figures) as described previously (3,4). To activate TRPV4 selectively, we took advantage of the TRPV4 agonist, GSK101, to demonstrate specific activation of TRPV4 (19,24). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1D, a. Exposure of brain slices to the selective TRPV4 agonist, GSK1016790A (hereafter GSK; 100 nM) (30), induced rapid, high-amplitude Ca 2+ oscillations in endfeet, increasing oscillation frequency by 417% ± 113% (Fig. 1C, b).…”
Section: Trpv4mentioning
confidence: 97%